The Pyramidal Method for Traveling Salesman Problem - Pesko, Stefan (Communications - Scientific letters of the University of Zilina, 2000)
A shortest pyramidal tour (SPT) is a well-solved case of TSP when a distance matrix is the Monge matrix. We study heuristic repeating method for SPT with the distance matrix without restriction. A new procedure for computing SPT is based on a shortest path in the network. Good results for solved the Euclidean TSP instances with the stochastic version of the demonstrated method are presented.